Вы находитесь на странице: 1из 8

# Solution to Exercises and Tutorial: Chapter 3

Example 1.
1A 1 i1 6 Ω i1 2 4A
i2 i3
1A
2Ω 7Ω 4A

At node 1,

v 1 − v 2 v1 − 0
1 = i1 + i2 1= +
6 2

or 6 = 4v1 - v2 (1)

At node 2,

v1 − v 2 v −0
i1 = 4 + i 3 = 4+ 2
6 7

## Solving (1) and (2) gives

v1 = –2 V, v2 = –14 V

2.
At node 1,

− v 1 v1 v − v2
− = 6+ 1 60 = - 8v1 + 5v2 (1)
10 5 2

At node 2,
v2 v − v2
= 3+6+ 1 36 = - 2v1 + 3v2 (2)
4 2

## Solving (1) and (2),

v1 = 0 V, v2 = 12 V

Problem
5A

8Ω
v0
v1
1Ω 2Ω
20 V –
4Ω +
+
40 V –

v1 − v 0 40 − v 0
At node 1, +5= v1 + v0 = 70 (1)
2 1

v1 − v 0 v v + 20
At node 0, +5= 0 + 0 4v1 - 7v0 = -20 (2)
2 4 8

## Solving (1) and (2), v0 = 27.27 V

*********************************************************************************************

Problem:
4Ω 3V
v v1 -+
7V + + + +
- 3Ω v 2Ω 6Ω
v v1
- - -

(a) (b)

## At the supernode in Fig. (a),

7 − v v v1 v1
= + +
4 3 2 6

or 21 = 7v + 8v1 (1)

## Applying KVL to the loop in Fig. (b),

- v - 3 + v1 = 0 v1 = v + 3 (2)
Solving (1) and (2),
v = – 0.2 V

v1
v1 = v + 3 = 2.8, i1 = = 1.4
2

i1 = 1.4 A

*************************************************************************************************

## Solution to Mesh Problem

10 Ω

i1
6V
2Ω
+–

1Ω
i2
4Ω + i3 5Ω
8V –

i
i2 i3
0

For loop 1,
6 = 12i1 – 2i2 3 = 6i1 – i2 (1)
For loop 2,
-8 = – 2i1 +7i2 – i3 (2)
For loop 3,

## We put (1), (2), and (3) in matrix form,

 6 − 1 0  i 1   3
 2 − 7 1 i  = 8 
  2   
0 − 1 6 i 3  2

6 −1 0 6 3 0
∆ = 2 − 7 1 = −234, ∆ 2 = 2 8 1 = 240
0 −1 6 0 2 6

6 −1 3
∆ 3 = 2 − 7 8 = −38
0 −1 2

∆3 − ∆2 − 38 − 240
At node 0, i + i2 = i3 or i = i3 – i2 = = = 1.188 A
∆ − 234

1.

v 2 − 12 v 0 v 0 − 10
i 1 + i2 + i3 = 0 + + =0
4 6 2

or v0 = 8.727 V
2.

v1 v 2
At the supernode, 5 + 2 = + 70 = v1 + 2v2 (1)
10 5

## Solving (1) and (2),

v1 = 18 V, v2 = 26 V
v1 v2
–+

5A 2A 8V
+ +
10 Ω 5Ω
v1 v2
– –

(a (b)
)

3.
i0 v0

2Ω
+ +
20V – 10V –

+ 4Ω
40V
1Ω

2Ω

## Using nodal analysis,

20 − v 0 40 − v 0 10 − v 0 v −0
+ + = 0 v0 = 20V
1 2 2 4

20 − v 0
i0 = = 0A
1

4.

5A

8Ω
v0
v1
1Ω 2Ω
20 V –
4Ω +
+
40 V –
v1 − v 0 40 − v 0
At node 1, +5= v1 + v0 = 70 (1)
2 1

v1 − v 0 v v + 20
At node 0, +5= 0 + 0 4v1 - 7v0 = -20 (2)
2 4 8

5.

4Ω 8Ω

i3 i4

2Ω 6Ω
+
30V –
i1 3Ω i2 1Ω

## For the supermesh, 6i3 + 14i4 – 2i1 – 6i2 = 0 (3)

But i4 – i3 = 4 which leads to i4 = i3 + 4 (4)